Women Trafficking Legislation in SAARC: A Cross-Country Comparative Study - Tahira Attia Fariha; Md Hasnath Kabir Fahim (APPTHI, 2024)
Human trafficking, defined by actions involving recruitment, transportation, harboring, and exploitation through force, deception, or coercion, has seen a significant surge in women trafficking across Asia in recent years. This escalation in women trafficking has resulted in adverse physical and psychological health conditions for victims, often leading to social disadvantages. Given the substantial representation of women in a nation's population, injustices against them can hinder a nation's development. Within the South Asian Association for Regional Cooperation (SAARC) region, member states while sharing similarities, exhibit significant variations in their anti-women trafficking policies. This disparity prompts questions regarding the relative strength of each country's anti-women trafficking laws. Focusing on Bangladesh as a SAARC member state, this paper conducts a comparative study of Bangladesh's anti-women trafficking laws with those of other SAARC countries to assess the impact and effectiveness of existing laws in combating women trafficking.